Efficacy of Herbomineral Toxin Binder ‘Vilocym Z’ in Amelioration of Mixed Mycotoxicosis in Broilers - Sawarkar, A.R.; Saxena, M.J.; Maini , S.; Ravikanth, K. (International Journal of Poultry Science, 2012)
A study was conducted in 72 day old Vencobb broiler chicks to evaluate toxic effects of aflatoxin B1 and ochratoxin A and efficacy of herbomineral toxin binder product Vilocym Z (supplied by Ayurvet Ltd., Baddi, India) in preventing co-mycotoxicosis. Chicks were randomly divided into three groups (n = 24) and each group having three replicated of 8 chicks each. Group I served as healthy Control (C) and given standard basal ration and no treatment, Group T0 and T1 birds were fed standard basal diet and mycotoxicated with 100 ppb each of aflatoxin B1 and ochratoxin A from 0-42 days. Group T0 is not given any treatment and served as positive control; however, mycotoxicated group T1 was administered herbomineral toxin binder product Vilocym Z@1kg/tonne of feed for 6 weeks. Mycotoxin adversely affected body weight gain, feed consumption, feed efficiency, haematobiochemical profile. However, supplementation of herbomineral toxin binder feed supplement has provided amelioration in mixed mycotoxicosis in broilers.